THE MALAYSIAN GOVERNMENT AND ECONOMIC SITUATION DURING THE COVID-19 PANDEMIC PERIOD - Mohamad, Ahmad Redzuan (Archives of Business Research, 2021)
This study was conducted to examine the extent to which the Covid-19 pandemic that hit the world has changed the economic position and government of Malaysian action in general and itself in particular. It not only looks at the economic context of the country but also looks at how the economy of the community itself was during this epidemic. It is done based on the situation that struck and the environmental conditions that can be seen in general. It will also look at how the economic position of individuals who have to change jobs to ensure family survival changes during this pandemic season. In other words, this is not just about national problems but more specifically about the economic position of Malaysian society itself in the face of the Covid-19 epidemic. There are individuals who are still able to survive with this current situation and not least also with individuals who are not able to survive with the pandemic that is plaguing this world. It does not matter whether a person is of high or low status. This study was conducted randomly on the Malaysian community by taking into account the various backgrounds of the community and the economic situation of Malaysia itself. This study also will look at the state of the Malaysian economy during the Covid-19 pandemic in two periods of rule. This can be seen due to the several changes of government leadership for some political reasons. However, all eras of government are active in fighting this pandemic despite the turbulent political issues.